Microgobius urraca (Teleostei: Gobiidae), a new species of goby from the tropical eastern Pacific - Tornabene, Luke; van Tassell, James L.; Robertson, D. Ross (Zootaxa, 2012)
A new species of goby in the genus Microgobius (Teleostei: Gobiidae: Gobiosomatini) is described from the Pacific coastof Panama. It is morphologically similar to M. erectus, but differs from that species in possessing fewer lateral scale rows,lacking a patch of ctenoid scales under the pectoral fin, having unpigmented epaxial myosepta, having a distinct oval-shaped dark blotch on the first dorsal fin, and possessing three blue-white stripes on a dark caudal fin. Differences in boththe number and type of scales, dorsal and anal fin ray counts, the poor development of a fleshy dorsal crest, and overallcolor patterns further distinguish this species from the remaining eastern Pacific congeners. Photographs of all Pacific species of Microgobius and a dichotomous key to the Pacific members of the genus are provided.